(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Infertility is a major concern among the people of reproductive age due to various causes. This is a case study of an infertile couple who had not been able to conceive for 2 years and 8 months of unprotected sexual life and had a history of abortion. Patient was diagnosed with PCOS (Polycystic Ovarian Syndrome). The objective of interventions included Ayurvedic management for abortion and ensuring nourishment of uterus and regular ovulation. This helps in facilitating healthy pregnancy and ensuring childbirth. Based on the parameters of Ayurveda, this case was diagnosed as Garbhasravi Vandhyatva (secondary infertility due to recurrent abortions). Treatment plan included both Shodhana (purification) followed by Uthara vasthi and Shamana (mitigation) therapies. The outcome of the Ayurvedic intervention was the conception of the patient after three courses of Ayurvedic treatments and was delivered with a healthy baby boy.